It’s a match: use of the radionuclide theranostic pair 133La/225Ac for the radiopharmacological characterization of EGFR-targeted single-domain antibodies - Johanna Trommer; Martin Ullrich; Falco Reissig; Santiago Andres Brühlmann; Anne-Kathrin Nitt-Weber; Zbynek Novy; Katarina Hajduova; Daniela Kurfurstova; Romana Hendrychova; Jan Bouchal; Milos Petrik; Christin Neuber; et al. (EJNMMI Radiopharmacy and Chemistry, 2025)
Abstract Background Targeted alpha therapy represents an advanced and rapidly evolving form of precision cancer treatment with increasing importance in recent years. The alpha-emitter 225Ac plays a key role in this clinical development due to its attractive physical and chemical properties. In this context, the macropa chelator has favorable characteristics in terms of labeling conditions and complex stability, making its derivatives exceptionally appealing for 225Ac-labeling of heat-sensitive biomolecules. However, preclinical evaluation of such 225Ac-containing molecules and comprehensive assessment of their pharmacokinetics, dosimetry and radiobiology necessitate a suitable diagnostic counterpart. Due to its attractive radiation properties, 133La represents an adequate positron-emitting radionuclide to form a matched pair with 225Ac for macropa-based radiopharmaceuticals. Herein, we describe the preparation and radiopharmacological characterization of macropa-functionalized, 133La/225Ac-labeled single-domain antibodies (sdAbs) targeting the epidermal growth factor receptor (EGFR) to demonstrate the general suitability of this theranostic pair of radionuclides. Results The synthesis of a clickable, bicyclononyne-modified macropa chelator and its site-specific conjugation to azide-modified, monovalent and biparatopic sdAbs is presented. Subsequent labeling at room temperature (rt) for 15 min resulted in molar activities of 30 MBq/nmol for 133La and 0.5 MBq/nmol for 225Ac, respectively. In vitro studies using the 133La-labeled sdAbs revealed comparable binding characteristics, but an enhanced cellular internalization of the biparatopic variant compared to its monovalent counterparts. This increased uptake consequently resulted in higher cytotoxicity of the 225Ac-labeled biparatopic conjugate. In vivo PET imaging of the 133La-labeled conjugates indicated comparable uptake and retention of the mono- and biparatopic variants in liver and kidneys, with the former showing slightly higher tumor accumulation. Ex vivo biodistribution studies conducted with 225Ac-labeled conjugates largely confirmed the findings obtained by PET imaging, albeit with a marginally higher tumor accumulation of the biparatopic 225Ac-radioimmunoconjugate. Final histological examinations of tumor and kidney tissues showed DNA damage in the renal cortex of the 225Ac-radioimmunoconjugate-treated mice, but no differences in the number of γ-H2AX-positive cells in the corresponding tumor tissues could be detected. Conclusions We present a comprehensive study on the theranostic application of 133La and 225Ac for antibody-based biomolecules and lay the foundation for the future application of this matched pair of radionuclides towards labeling of heat-sensitive, macropa-functionalized radiopharmaceuticals in general.